2007
DOI: 10.1111/j.1745-7254.2007.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TGF-?/Smad signaling pathway on lung myofibroblast differentiation

Abstract: Aim: Myofibroblasts play important roles in the pathogenesis of lung fibrosis. Transforming growth factor (TGF)‐β1 has been widely recognized as a key fibrogenic cytokine. The major signaling pathway of TGF‐β1 is through cytoplasmic Smad proteins. Our study investigated the role of individual TGF‐β1/Smad signal proteins in mediating α‐smooth muscle actin (α‐SMA) gene expression, which is a well‐known key marker of myofibroblast differentiation. Methods: We transiently cotransfected α‐SMA promoter‐luciferase fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
116
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(123 citation statements)
references
References 34 publications
6
116
0
1
Order By: Relevance
“…Canonical TGFb signaling is not altered in Postn 2/2 fibroblasts TGFb is known to cause an increase in a-SMA expression through phosphorylation of Smad3 (Gu et al, 2007), and plays a major role in myofibroblast differentiation (Desmouliere et al, 1993). Therefore, to determine whether the reduction in a-SMA expression and immunoreactivity in Postn 2/2 granulation tissue was due to defective TGFb-Smad3 signaling, we assessed the number of nuclei positive for phosphorylated Smad2 and Smad3 (Smad2/3-P) within the granulation tissue.…”
Section: Loss Of Periostin Results In Altered Wound-closure Kineticsmentioning
confidence: 99%
“…Canonical TGFb signaling is not altered in Postn 2/2 fibroblasts TGFb is known to cause an increase in a-SMA expression through phosphorylation of Smad3 (Gu et al, 2007), and plays a major role in myofibroblast differentiation (Desmouliere et al, 1993). Therefore, to determine whether the reduction in a-SMA expression and immunoreactivity in Postn 2/2 granulation tissue was due to defective TGFb-Smad3 signaling, we assessed the number of nuclei positive for phosphorylated Smad2 and Smad3 (Smad2/3-P) within the granulation tissue.…”
Section: Loss Of Periostin Results In Altered Wound-closure Kineticsmentioning
confidence: 99%
“…PTEN deficiency has been reported to be associated with fibrosis (30). Furthermore, TGF␤1 was shown to simultaneously activate phosphorylation of the Smad3 signaling pathway in fibroblasts (31). Immunohistochemical analysis suggested that treatment with FTY720 markedly decreased the infiltration of CD3ϩ cells, CD4ϩ T cells, and CD11bϩ monocyte/macrophages into the skin 42 days after BMT.…”
Section: Discussionmentioning
confidence: 99%
“…The switch of epithelial cells towards a mesenchymal phenotype is unfavourable and leads to the disruption of epithelial layers and functions [4]. TGF-β1 expression is elevated during fibrosis in several animal and human models [59]. However, despite being members of the TGF-β superfamily, few studies have addressed the role of BMPs in fibrosis.…”
Section: Bmps Emt and Fibrotic Diseasementioning
confidence: 99%